A comprehensive analysis of the uterine microbiome in endometrial cancer patients - identification of Anaerococcus as a potential biomarker and carcinogenic cofactor - Olga Kuźmycz; Aleksandra Kowalczyk; Aleksandra Bolanowska; Anna Drozdzowska; Jakub Lach; Jakub Lach; Wiktoria Wierzbińska; Wiktoria Wierzbińska; Tomasz Kluz; Tomasz Kluz; Paweł Stączek (Frontiers in Cellular and Infection Microbiology)
IntroductionEndometrial cancer (EC) is a significant gynecological malignancy with increasing incidence worldwide. Emerging evidence highlights the role of the uterine microbiome in the pathogenesis of EC. This study aims to characterize the uterine microbiome in EC patients and identify potential microbial biomarkers, with a focus on Anaerococcus as a differentiating taxon.MethodsThe endocervical canal swabs from patients with EC (n=16) and non-cancerous patients (EM, n=13) were collected. The V3-V4 region of the 16S rRNA gene was sequenced using the Illumina platform. Bioinformatic analyses were performed with QIIME2, and statistical comparisons were conducted to assess differences in microbial composition and diversity. In vitro experiments were conducted to assess the functional impact of Anaerococcus on human uterine fibroblasts, including its ability to adhere to the human cells and induce oxidative stress.ResultsThe α-diversity metrics, including Shannon entropy and observed amplicon sequence variants (ASVs), revealed significantly higher microbial diversity in EC samples compared to EM. Anaerococcus was identified as a key taxon differentiating EC from EM groups, showing a higher relative abundance in EC samples. Functional predictions and in vitro assays indicated that Anaerococcus may contribute to carcinogenesis by inducing reactive oxygen species (ROS) production, and has the high ability to adhere to the human endometrial fibroblasts.DiscussionThe study provides evidence of distinct microbial signatures in EC, with Anaerococcus emerging as a potential biomarker. The in vitro findings suggest its role in endometrial carcinogenesis, underscoring its potential as a target for future diagnostic and therapeutic applications.